2008
DOI: 10.1111/j.1600-051x.2008.01317.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of treatment on soluble tumour necrosis factor receptor type 1 and 2 in chronic periodontitis

Abstract: The ratio of sTNFR2/R1 in GCF significantly increased after treatment, and could be related to the clinical state of CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 30 publications
3
34
0
Order By: Relevance
“…The systemic levels of TNF‐α in subjects with periodontitis and the impact of periodontal therapy on circulating TNF‐α concentrations remain controversial 21,29‐38 . In agreement with the present study, a previous report 29 did not find differences in the serum levels of TNF‐α between PH subjects and subjects with CP.…”
Section: Discussionsupporting
confidence: 83%
“…The systemic levels of TNF‐α in subjects with periodontitis and the impact of periodontal therapy on circulating TNF‐α concentrations remain controversial 21,29‐38 . In agreement with the present study, a previous report 29 did not find differences in the serum levels of TNF‐α between PH subjects and subjects with CP.…”
Section: Discussionsupporting
confidence: 83%
“…Additional studies revealed that following therapy, the level of IL-1β in the GCF was reduced (9), while the total level of IL-10 remained unchanged (10). In addition, a previous study did not identify a statistically significant difference in the total amount of TNF-α prior to and following periodontal treatment in chronic periodontitis subjects (11). Despite the apparent general consensus of a decrease in proinflammatory cytokines following nonsurgical therapy, certain studies have not produced such observations.…”
Section: Discussionmentioning
confidence: 87%
“…Navarro‐Sanchez et al 13 found a significant reduction in the levels of TNF‐α in the GCF after periodontal therapy in subjects with and without diabetes. Ikezawa‐Suzuki et al 14 observed that TNF‐α levels in the GCF of smokers and non‐smokers with chronic periodontitis did not change significantly after periodontal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TNF‐α may significantly stimulate local bone resorption by inducing osteoclastogenesis and influencing the production of the essential osteoclast differentiation factors, such as receptor activator of nuclear factor‐kappa B ligand and its soluble decoy receptor, osteoprotegerin 7 . The presence of TNF‐α in the gingival crevicular fluid (GCF) has been investigated in several studies 8–14 . However, fewer studies 15–19 have assessed the presence of TNF‐α in peri‐implant crevicular fluid (PICF).…”
mentioning
confidence: 99%